Systematic study of fission modes in the proton-induced fission of actinide and pre-actinide. (13th December 2017) - Andrade-II, E; Karapetyan, G S; Deppman, A; Bernal-Castillo, J L; Guimarães, Valdir; Balabekyan, A R; Adam, J; Garcia, F; Guzmán, F
Abstract: The systematic analysis of several measured fragment mass distributions from different fission reactions available in the literature is presented. Data of proton-induced fission on 241 Am, 237 Np and 238 U measured at 26.5, 62.9 and 660 MeV, on 232 Th measured at 26.5, 62.9 and 190 MeV, on 208 Pb measured at 190, 500 and 1000 MeV and on 197 Au measured for 190 and 800 MeV protons has been analyzed and studied in the framework of the Random Neck Rupture Model. New data on mass distribution for fission fragments from 241 Am proton-induced fission at 660 MeV measured at the LNR Phasotron (JINR) are also presented. The roles of the neutron excess and of the so called fissility parameter were also investigated.